Bioinformation worlds and futures
1 online resource
Keywords: "This book sets out to define and consolidate the field of bioinformation studies in its transnational and global dimensions, drawing on debates in science and technology studies, anthropology and sociology. It provides situated analyses of bioinformation journeys across domains and spheres of interpretation. As unprecedented amounts of data relating to biological processes and lives are collected, aggregated, traded and exchanged, infrastructural systems and machine learners produce real consequences as they turn indeterminate data into actionable decisions for states, companies, scientific researchers and consumers. Bioinformation accrues multiple values as it transverses multiple registers and domains, and as it is transformed from bodies to becoming a subject of analysis tied to particular social relations, promises, desires and futures. The volume harnesses the anthropological sensibility for situated, fine-grained, ethnographically grounded analysis to develop an interdisciplinary dialogue on the conceptual, political, social and ethical dimensions posed by bioinformation"--